2005
DOI: 10.1111/j.1475-097x.2005.00653.x
|View full text |Cite
|
Sign up to set email alerts
|

Linear and non‐linear heart rate variability measures in chronic and acute phase of anorexia nervosa

Abstract: Previous results on heart rate variability (HRV) analysis in anorexia nervosa (AN) include some apparently conflicting data. In order to find out the reason for different results and to improve understanding of autonomic control in AN we compare HRV in acute and chronic AN. Spectral powers, fractal scaling exponent and sample entropy were computed from 24 h RR series derived from Holter ECG recordings in 17 anorexic patients, nine chronic and eight healthy women. We found that all linear and non-linear HRV mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 44 publications
2
24
0
Order By: Relevance
“…However, the evidence from these data is poor as they were collected in 6 patients only. Similar data were obtained by Platisa, Nestorovic, Damjanovic and Gal (2006). Results of this study also point to decreased sympathetic modulation in chronic AN and an increased parasympathetic modulation in acute AN.…”
Section: Studies Using 24-hour Recordingsupporting
confidence: 90%
“…However, the evidence from these data is poor as they were collected in 6 patients only. Similar data were obtained by Platisa, Nestorovic, Damjanovic and Gal (2006). Results of this study also point to decreased sympathetic modulation in chronic AN and an increased parasympathetic modulation in acute AN.…”
Section: Studies Using 24-hour Recordingsupporting
confidence: 90%
“…Studies on the changes in HRV following orthostatic challenge in AN patients have not produced consistent findings [27,2,36,28,32]. The time and frequency domain analysis in seated subjects showed no significant differences between the control and AN group in agreement with some previous studies [26,24,37].…”
Section: Hrv Measuressupporting
confidence: 76%
“…Platisa et al (2006) evaluated linear and non-linear measures of HRV, and found differences in both measures in acute and chronic AN patients over a 24-h assessment period. Specifically, acute AN was characterized by decreased HR and increased HRV, whereas chronic AN patients showed increased HR, reduced HRV and higher differences between awakening and sleeping conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, almost 80% of AN patients have cardiovascular abnormalities, mainly bradycardia, hypotension, arrhythmias and repolarization disorders. Additionally, AN patients may present with reduced left ventricular mass (Galetta et al 2003;Romano et al 2003) and alterations in sympathovagal balance (Kollai et al 1994;Kreipe et al 1994;Petretta et al 1997;Rechlin et al 1998;Casu et al 2002;Galetta et al 2003;Cong et al 2004;Melanson et al 2004;Platisa et al 2005;Platisa et al 2006), the latter being of parrticular relevance in increasing the risk of cardiovascular mortality and sudden death in AN (Neumarker 1997).…”
Section: Introductionmentioning
confidence: 98%